2015
DOI: 10.1088/0022-3727/48/33/335304
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide sorption in a nanoporous octahedral molecular sieve

Abstract: We have performed first-principles density functional theory calculations, incorporated with van der Waals interactions, to study CO2 adsorption and diffusion in nanoporous solid -OMS-2 (Octahedral Molecular Sieve). We found the charge, type, and mobility of a cation, accommodated in a porous OMS-2 material for structural stability, can affect not only the OMS-2 structural features but also CO2 sorption performance. This paper targets K + , Na + , and Ba 2+ cations. First-principles energetics and electronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…With β = ~ 97 0 and α = γ = ~90°, the OMS-5 cell remains monoclinic in the presence of Na + cations. However, the cell volume shrinks by 0.3% with a low concentration of Na + cations and 0.8% with a high concentration of Na + cations, which also happens in the OMS-2 materials (Williamson et al , 2015). The volume decrease is the concequence of the shorter tunnel length along the b axis.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…With β = ~ 97 0 and α = γ = ~90°, the OMS-5 cell remains monoclinic in the presence of Na + cations. However, the cell volume shrinks by 0.3% with a low concentration of Na + cations and 0.8% with a high concentration of Na + cations, which also happens in the OMS-2 materials (Williamson et al , 2015). The volume decrease is the concequence of the shorter tunnel length along the b axis.…”
Section: Resultsmentioning
confidence: 95%
“…These data confirm that OMS-5 demonstrates semiconducting behavior. Like OMS-2, the DoS of OMS-5 shifts to the lower energy values in the presence of Na + cations (Williamson et al ., 2015). This shift stems from the Na + donating electrons to the OMS-5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing research has demonstrated the potential of micro-nanofluidic technology in CO 2 capture. Currently, CO 2 capture technologies mainly include absorption, adsorption [43][44][45], and membrane separation. Absorption methods involve physical and chemical absorption, which utilize organic solvents or alkaline solutions with high solubility, selectivity, and stability to separate CO 2 .…”
Section: Research On Co 2 Capturementioning
confidence: 99%